Broadband BiOCl Nonlinear Saturable Absorber for Watt‐Level Passively Q‐Switched Yb:LuAG Single Crystal Fiber Laser. Issue 22 (21st August 2022) - Ma, Xiaofei; Wang, Ci; Zhang, Jian; Wang, Tao; Wang, Anye; Wang, Siyuan; Jia, Zhitai; Zhang, Baitao; He, Jingliang; van Smaalen, Sander; Tao, Xutang
Abstract: The development of nonlinear optical (NLO) devices is limited to the mid‐infrared range due to the lack of broadband NLO response. As an indirect band gap semiconductor, BiOCl has a band gap of ≈3.3 eV. The special anisotropic lamellar structure makes it exhibit excellent electrical and optical properties; however, its NLO saturable absorption effect is rarely reported. In this study, the NLO response, optical properties, and applications of BiOCl crystals grown by chemical vapor phase transport method are studied in detail. The transmission spectrum indicates the BiOCl crystal has a broadband transparent region (0.4–11 µm). The saturable absorption of BiOCl is characterized by the Z‐scan method with 532 and 1030 nm pulsed lasers. With BiOCl as the saturable absorber (SA), watt‐level passively Q‐switched pulsed laser based on Yb:LuAG single crystal fiber (SCF) is realized. This is the first report of BiOCl as SA for passively Q‐switched all‐solid‐state pulsed laser, and the obtained average power is the highest value of passively Q‐switched SCF pulsed lasers reported so far. The high transmittance, high laser damage threshold, wideband NLO response, and environmental stability of BiOCl indicate that BiOCl crystal is a potential candidate for NLO applications. Abstract : The nonlinear optical properties of BiOCl crystal, which has a broadband (visible–infrared) nonlinear saturable absorption and a high laser damage threshold to be a saturable absorber of broadband high‐power laser, are studied. Combining BiOCl with single‐crystal fiber for the first time, a watt‐level passively Q‐switched Yb:LuAG single‐crystal fiber laser is realized.